Children of fisherfolks their socio-economic roles, work participation in fishing activities and life aspirations - Eñano, Carissa Ann M.
This is a descriptive study aimed to determine the socio-economic roles, work participation in fishing activities and life-aspirations of children of fisherfolks. The study hypothesized that: 1) children play socio-economic roles, 2) children of fisherfolks participate actively in fishing activities, and 3) children aspire more in life than participating only in fishing activities., Thirty-four (34) male and twenty-six (26) female children with seven (7) to seventeen (17) years of age served as participants for this study. an interview guide was utilized for socio-economic roles, work participation and life-aspirations. A seasonal calendar, a 24-hour activity recall and a checklist of fishing activities of both male and female children. The responses were analyzed through the frequency and mean to know what are the most commonly shown activities and life-aspirations that the male and female children exhibit. These statistical tools were also utilized to determine how active the participants were in the different activities. It was found out that dominantly, children play socio-economic roles. It was usually to help in community development and to earn money through fishing. The male fisherfolk children participated more in fishing activities with a mean of 2 (slightly active), while the females only have the mean of (inactive). Most of the participants aspired to finish their education and acquire high paying jobs in order to help their family. They also expressed the desire for improvements in their community's external environments as well as the strict implementation of fishing laws.